Penerapan Simple Additive Weighting dalam Sistem Pendukung Keputusan Pemilihan Pelanggan Terbaik pada PT Fartan Energy - Jayanti, Nila Rusiardi (Komputa : Jurnal Ilmiah Komputer dan Informatika, 2025)
PT Fartan Energy operates in the marine service, oil and gas sectors. This company has existed for 19 years and has many partners/customers. To further strengthen the partner/customers who collaborate with this company, the author created a design for a Decision Support System to select customers at PT Fartan Energy using the Simple Additive Weighting (SAW) method. By creating this system, the aim is to select loyal partners who will be given rewards as a form of appreciation to strengthen cooperative relationships. The method used in the decision support system is Simple Additive Weighting. The SAW method combines several criteria and assigns weights to each criterion to evaluate the best customers. There are 4 criteria used in this research, namely shopping total, shopping activity, customer income, and customer address. In creating the SPK design, NetBeans software, was used the Java programming language and MySQL database. The output of this SPK is a final report in the form of who is selected as a loyal customer and will be given a reward. In this research there were 5 partners who were evaluated based on 4 assessment criteria. The rangking results show that alternative A3 got the highest score, namely the partner is Job Pertamina – Meco E&P Simenggaris with a final score 100, so it was decided as the best partner of PT Fartan Energy. The best partenrs will be given appreciation, so it is hoped that they can increase cooperation and also increase company profits.